Eradication of Helicobacter pylori for prevention of aspirin-associated peptic ulcer bleeding in adults over 65 years: the HEAT RCT - CJ Hawkey; Anthony J Avery; Carol AC Coupland; Colin J Crooks; Jennifer S Dumbleton; FD Richard Hobbs; Denise Kendrick; Michael Moore; Clive Morris; Gregory Rubin; Murray Smith; Diane Stevenson (Health Technology Assessment)
Background Peptic ulcers in patients on aspirin are associated with Helicobacter pylori infection. We investigated whether H. pylori eradication would protect against aspirin-associated ulcer bleeding. Methods The Helicobacter Eradication Aspirin Trial was a randomised placebo-controlled trial (European Union Drug Regulating Authorities Clinical Trials 2011-003425-96), conducted in United Kingdom primary care using routinely collected clinical data. Consenting participants aged ≥ 60 years prescribed aspirin ≤ 325 mg but not ulcerogenic or gastroprotective medication underwent C13 urea breath testing for H. pylori. Those with a positive test were randomised to receive either a combination of clarithromycin 500 mg, metronidazole 400 mg and lansoprazole 30 mg, or placebos twice daily for 7 days. The primary outcome, time to death or hospitalisation due to peptic ulcer bleeding, was analysed using a Cox proportional hazards model. Findings Between 14 September 2012 and 22 November 2017, 30,166 participants underwent H. pylori breath testing, 5367 had a positive result, 5352 were randomised to an intention-to-treat population of 2677 (eradication) and 2675 (placebo) and followed up for a median of 5.0 years (interquartile range 3.9–6.4). Statistical analysis of the primary outcome showed an overall hazard ratio of 0.69 [95% confidence interval 0.38 to 1.25; p = 0.22], but there was a significant departure from the proportional hazards assumption (p = 0.0068), requiring analysis split at the median time to event: 2.5 years. There was a significant reduction in the primary outcome in the eradication treatment group in the first 2.5 years (hazard ratio 0.35, 95% confidence interval 0.14 to 0.89; p = 0.028) but not the second period (hazard ratio 1.31, 95% confidence interval 0.55 to 3.11). The number needed to treat (first period) was 238 (95% confidence interval 184 to 1661). Results in the first 2.5 years remained significant when accounting for the competing risk of death (p = 0.028). During the study period, 657 participants died (306 in the eradication group and 351 in the controls group; hazard ratio 0.86, 95% confidence interval 0.74 to 1.01; p = 0.058). Malignancy was the most common cause of death and largely accounted for the numerical difference between the treatment groups. A health economic analysis found proactive screening not cost-effective, since the monetised benefits of the intervention in preventing a peptic ulcer bleed failed to outweigh the costs. Interpretation Helicobacter pylori eradication protects against aspirin-associated peptic ulcer bleeding, but this may not be sustained or cost-effective when applied non-selectively to our study population. The possibility that H. pylori eradication, on a background of aspirin use, might affect death from malignancies warrants further evaluation. Limitations and future work Studying subjects already established on aspirin probably contributed to the low event rate. A future study should investigate subjects starting on aspirin when the event rate is higher. Trial registration This trial is registered as ISRCTN10134725; ClinicalTrials.gov number NCT01506986. Funding This award was funded by the National Institute for Health and Care Research (NIHR) Health Technology Assessment programme (NIHR award ref: 09/55/52) and is published in full in Health Technology Assessment; Vol. 29, No. 42. See the NIHR Funding and Awards website for further award information. Plain language summary Background Low-dose aspirin is valuable in protecting people at increased risk from having heart attacks and strokes, but increases the risk of bleeding, particularly from stomach ulcers. The main cause of stomach ulcers is the bacteria Helicobacter pylori. We carried out a trial to test whether antibiotic treatment to eradicate Helicobacter pylori would protect participants from ulcer bleeding. Methods General practitioners in 1208 United Kingdom general practices searched their records to find people aged 60 and over who were taking low-dose aspirin. We used a breath test to detect H. pylori infection. Those with a positive result were randomly assigned to receive well-established eradication treatment with two antibiotics (clarithromycin and metronidazole) and a drug that reduces stomach acidity (lansoprazole), or matching placebos (dummy pills) twice daily for a week. We used routinely collected general practitioner and hospital data and death certificates to see if the treatment reduced the outcome of hospitalisation or death from ulcer bleeding. Findings We breath tested over 30,000 people. Over 5000 tested positive and were randomly assigned to receive active treatment (2677 people) or placebos (2675 people). Over an average of 5 years’ follow-up, 44 people were hospitalised because of ulcer bleeding. People who had received active treatment were 65% less likely to develop ulcer bleeding in the first 2.5 years compared to those who had received placebos. However, this benefit reduced after longer follow-up, and there was no difference between the treatments when data from beyond 2.5 years were included in the analysis. H. pylori eradication was not cost-effective because of the large number of subjects that needed to be treated to prevent one ulcer bleed. Conclusion Helicobacter pylori eradication protects against ulcer bleeding in people on aspirin, but this may not be sustained. Scientific summary Aspirin in low doses (≤ 325 mg daily) is useful in reducing the risk of myocardial infarction (MI) and thrombotic stroke, but its use is limited by adverse events (AEs), principally bleeding, from the gastrointestinal (GI) tract. Meta-analyses show that peptic ulcers and upper gastrointestinal bleeding (UGIB) that occur in patients on aspirin are associated with Helicobacter pylori infection. Two studies of eradication in aspirin users who have already presented with an ulcer bleed have yielded inconsistent results, and there are no data on the effect of H. pylori eradication on ulcer bleeding at a population level. We therefore investigated the hypothesis that H. pylori eradication would protect against aspirin-associated ulcer bleeding. Methods The Helicobacter Eradication Aspirin Trial (HEAT) was a randomised placebo-controlled trial conducted in UK primary care which used routinely collected clinical data to identify possible participants and to follow clinical progress. It was conducted in 1208 UK primary care practices, of which 1055 enrolled at least one participant. Recruitment Consenting participants aged ≥ 60 years who were prescribed aspirin (≤ 325 mg) but not ulcerative or gastroprotective medication made a single baseline trial visit for collection of clinical data and underwent a C13 urea breath test for H. pylori. Those with a positive test were randomised to receive either a combination of clarithromycin 500 mg, metronidazole 400 mg and lansoprazole 30 mg or placebo twice daily for 7 days. Participants were asked to record the timing of each dose and record all possible side effects. Those recording taking at least eight doses formed the per-protocol population. Follow-up Outcomes were ascertained from electronic general practice records, Hospital Episode Statistics (HES) and Office for National Statistics mortality data. A randomly selected sample underwent repeat breath testing at the end of the study. Outcomes The primary outcome was time to hospitalisation or death due to definite or probable peptic ulcer bleeding (including gastric, duodenal and oesophageal ulcer bleeds). All plausible events which mentioned GI bleeding or peptic ulcer in any of the outcome data sources were evaluated by a blinded adjudication committee comprising three specialist clinicians. The initial published protocol omitted to mention death due to peptic ulcer bleeding, noted while planning the statistical analysis after the trial had finished, but before the code was broken. Both hospitalisation and death categories were then explicitly included in the primary outcome in the planned analysis, although there were in fact no pre-hospitalisation peptic ulcer deaths. Secondary outcomes were hospitalisation or death from gastroduodenal ulcer bleeds (oesophageal lesions excluded), clinically evident bleeds from other conditions, uncomplicated ulcers, consultations for dyspepsia, changes in selected drug prescription and thrombotic cardiovascular (CV) outcomes. Statistics and power An intention-to-treat (ITT) analysis was carried out including all randomised participants irrespective of whether they took the treatment, or the number of doses taken. The analysis of the primary outcome was based on time to first event. A Cox proportional hazards model adjusted for regional centre as a fixed effect was used to calculate hazard ratios (HRs) and 95% confidence intervals (CIs) comparing the two treatment groups. The assumption of proportional hazards was tested using scaled Schoenfeld residuals and assessed graphically by a log minus log plot. Where there was clear evidence of violation of this assumption, HRs were calculated for two separate periods of follow-up split at the median time to event after randomisation. To calculate sample size, we assumed a background event rate of 8/1000 ulcer bleeds per year and hypothesised that eradication treatment would reduce this by 50%. In order to detect this effect with 90% power, 87 primary outcome events were required. Primary outcomes occurred at a slower rate than expected, and the trial was stopped after 44 outcomes had occurred. Results Between 14 September 2012 and 22 November 2017, 30,166 participants underwent breath testing, of whom 5367 had a positive result and 5352 were randomised to an ITT population of 2677 (eradication treatment) and 2675 (placebo). Baseline characteristics Median age at consent was 73.6 (standard deviation 6.9) years, and 72.8% of the participants were male. Coronary heart disease was the most common comorbidity among aspirin indications (49.2%), and 10.0% were taking nitrates. More than half the participants (52.8%) were ex-smokers, but a history of peptic ulcer was uncommon (1.8%). Treatment adherence Treatment diaries were not returned by 432 participants (16.1%) in the control group and 418 (15.6%) in the eradication group. Of the 2675 participants in the control group, 2133 (79.7%) returned a record of having taken all 14 doses, and 2226 (83.2%) reported taking at least 8 doses. Fewer participants in the eradication group reported adherence to treatment: 1966 (73.4%) took all 14 doses, and 2143 (80.1%) reported taking at least 8 doses (p = 0.003 vs. controls). Follow-up rates Randomised participants were followed up for a total of 26,668 person-years [median 5.0 years, interquartile range (IQR) 3.9–6.4 years]. Seventy-one participants (1.3%) withdrew consent to further data follow-up at a median value of 503 days (IQR 69–1324) after randomisation. Helicobacter pylori clearance In the 10% sample of participants receiving a repeat breath test, a median of 3.95 (IQR 2.76–5.28) years after randomisation, the test was negative in 146 of 161 participants in the eradication group (90.7%) versus 41 of 161 (24.0%) in the control group (p < 0.001). Primary outcome In total, 44 participants had an episode that was adjudicated as a primary outcome, comprising 18 in the active eradication group and 26 in the control group. The overall HR comparing the eradication treatment group with the control group was 0.69 (95% CI 0.38 to 1.25; p = 0.22), but a Schoenfeld analysis showed a deviation from the proportional hazards assumption (p = 0.0068). Accordingly, we fitted one Cox model with a time split in the data at the median of 2.5 years’ follow-up. This resulted in the Cox proportional hazards assumptions being met (p = 0.54 for the overall model). Two and a half years were selected prior to the unblinding of the data as the time point, with equal numbers of events and follow-up in both periods. Primary end point: split time analysis There were 23 episodes of the primary outcome of ulcer bleeding in the first 2.5 years (6 in the eradication group and 17 in the control group), with a rate of 0.92 (95% CI 0.41 to 2.04) per 1000 person-years in the eradication group and 2.61 (95% CI 1.62 to 4.19) per 1000 person-years in the control group. In the ITT analysis, there was a significantly reduced HR in the first 2.5 years for eradication treatment versus control of 0.35 (95% CI 0.14 to 0.89; p = 0.028) and a number needed to treat (NNT) of 238 (95% CI 184 to 1661). There were 21 episodes (12 in the eradication group and 9 in the control group) for follow-up after 2.5 years, with no significant difference between groups [HR 1.31 (95% CI 0.55 to 3.11); p = 0.540]. In the per-protocol analysis of 4369 participants who had taken at least 8 doses of treatment, the rates in the first 2.5 years were 0.57 (0.18 to 1.76) per 1000 person-years in the eradication arm and 2.75 (1.66 to 4.56) per 1000 person-years in the control group, and the HR was 0.21 (95% CI 0.06 to 0.71; p = 0.013). Sensitivity analyses The ITT hazard reduction remained significant in sensitivity analyses adjusting for age and sex and for time-varying drug use as well as in a Fine–Gray analysis adjusted for the competing risk of death. Secondary outcomes Hospitalisation for gastric or duodenal ulcer bleeds In an analysis restricted to participants with bleeding from gastric or duodenal ulcers (oesophageal ulcers excluded), the proportional hazards assumption was not met, and data were again analysed on a split time basis. In the first 2.5 years of follow-up, there were 5 hospitalisations for ulcer bleeding in the eradication group compared to 16 in the control group, with a significant HR of 0.31 (95% CI 0.11 to 0.85; p = 0.023). Other secondary outcomes For all other secondary analyses based on time to event, proportional hazards assumptions were supported so analyses covered the whole unsplit follow-up time. There were no significant differences between the two treatment groups for any of the following end points: Other causes of GI bleeding: there were 97 episodes of clinically evident GI bleeding from causes other than peptic ulcers, 51 (1.9%) participants in the eradication group versus 46 (1.7%) in the control group. Uncomplicated ulcers: there were 67 participants (2.5%) with an uncomplicated peptic ulcer in the eradication group compared to 66 (2.5%) in the control group. Consultations for dyspepsia: in the eradication group, 68 participants (2.5%) had between 1 and 5 primary care consultations for dyspepsia during follow-up compared to 66 (2.5%) in the control group. CV outcomes: there were 149 participants in the active eradication group (5.6%) who had a CV outcome (85 MI, 54 stroke, 10 both) versus 169 (6.3%) control participants (100 MI, 67 stroke, 2 both), with a HR of 0.87 (95% CI 0.70 to 1.09; p = 0.23). Changes in drug use: prescriptions of aspirin fell progressively throughout the follow-up period. After 2.5 years of follow-up, 82.4% of those in the eradication group and 82.6% in the control group were still taking aspirin. The point prevalence of proton pump inhibitor (PPI) prescription increased progressively throughout follow-up: after 2.5 years 12.5% and 12.3% of those in the eradication and control groups, respectively, were prescribed a PPI. Few participants received antacids or histamine2 receptor antagonists (H2RAs). Adverse events There were 5293 reports of AEs (4006 in the eradication group, 1287 in the control group) in the 4 weeks from the start of trial treatment. This high frequency of AEs reflects the proactive collection via participant completed diaries. The pattern of reported AEs was similar to that already recognised for the drugs used. The most common were taste disturbance, diarrhoea and abdominal pain. Deaths In total, 657 participants died during follow-up [306 in the eradication group and 351 in the control group (HR 0.86, 95% CI 0.74 to 1.01; p = 0.058)]. The numerical difference was largely attributable to deaths due to malignancy. Health economics Out of the primary outcome analysis, the estimate of the NNT to prevent one peptic ulcer bleed was 238. Consequently, the costs of preventing a single peptic ulcer bleed using the HEAT proactive screening intervention were now expected to be substantial, where the cost incurred to screen, test and treat just one person was approximately £40 in 2020–1 prices. We used a decision tree model to account for other elements of the intervention: people refusing invitations to screen, people screened but returning a negative breath test and therefore not treated, and people with treatment side effects. From it, the cost for proactive screening to prevent just one peptic ulcer bleed were estimated to exceed £58,000. Two factors arising when a peptic ulcer bleed occurs are avoided under the intervention and therefore defray the prevention cost: (1) the monetised value of the patient loss [valued at the National Institute for Health and Care Excellence (NICE) threshold £20,000/quality-adjusted life-year (QALY)] and (2) the cost of hospitalisation for a bleed. For the latter, HES data were used to obtain the mean cost of hospitalisation associated with the trial primary outcome: eradication £3790 (95% CI £2117 to £5462) and control £3326 (95% CI £2094 to £4559) which did not differ significantly (p = 0.657). The other, patient loss, was assessed to be £810 using an area under the curve approach, the data for which came from responses to EuroQol-5 Dimensions, five-level version (EQ-5D-5L) obtained from those selected into the 10% resample group. Neither (1) and (2) alone or in combination fail to outweigh the costs of prevention [i.e. net monetary benefit (NMB) is negative-valued] and thus proactive screening is here not judged to be cost-effective. Discussion This report describes the results of a clinical trial conducted in primary care and using routinely collected clinical data to assess the effects or H. pylori eradication on subsequent ulcer bleeding. This was assessed using hospitalisation or death due to peptic ulcer bleeding as the primary outcome. Omitting mention of death due to peptic ulcer bleeding from the protocol was an error, but it did not affect the analysis, as there were no pre-hospitalisation deaths. The incidence of outcome events was lower than anticipated, and the trial was stopped before the intended number had accrued. Nevertheless, the trial was able to detect a biphasic pattern of results during follow-up. In the first time period, set at the median of 2.5 years after randomisation, there was a significant 65% reduction in the primary outcome following eradication compared to control treatment, which was particularly evident in the first 17.5 months when none of the participants that had received active eradication treatment developed ulcer bleeding. Thereafter, there was a progressive development of ulcer bleeding so that in the period beyond 2.5 years, there was no significant difference between the two groups. The trial was conducted at a time when prescribing policies and attitudes to aspirin and coprescription of protective drugs were changing. This could have confounded our results, but the differences between the two groups remained significant when adjusted for time-varying drug use as well as for age, sex and the competing risk of death. The reasons for the loss of the early benefit of eradication at later time points are unclear. We cannot definitively rule out reinfection or recrudescence of H. pylori infection as the cause, although this would be unusual for adults in this situation. Similarly, the time course makes a persistent but ultimately transitory effect of lansoprazole from the eradication regimen unlikely. H. pylori provokes an inflammatory response and enhances release of protective mediators such as prostaglandins: this could be lost over time. H. pylori eradication can lead to both increased or decreased acid secretion, but there is no direct evidence to make these possibilities anything other than speculative. The findings of HEAT extend the range of patients for whom H. pylori eradication is indicated from secondary prevention of recurrent bleeding to patients on aspirin chronically who have not yet had an ulcer bleed. However, most of these patients will not develop this outcome, so that the NNT is high, making an unselective test-and-treat strategy that is not cost-effective. H. pylori eradication should be reserved for patients at higher risk. Epidemiological evidence suggests that risks are high during the first year of starting aspirin. This would be an appropriate scenario for future research. However, the loss of benefit with time should be factored into policy and research protocols. Among secondary end points, there was no significant difference in the incidence of uncomplicated ulcers or thrombotic CV events, and the incidence of consultations for dyspepsia was low: this may be because antisecretory drug use was an exclusion criterion which excluded those using these drugs for dyspepsia treatment. This study has developed a novel infrastructure and shown that it can be used for therapeutic research in primary care. The study had some weaknesses, particularly relating to the problems of generating a sufficient number of primary outcome events. These were largely study specific. Building on experience from HEAT, improvements in methodology, particularly with regard to timely automated acquisition of data, mean that a resource for the effective conduct of large trials in primary care has been established. Trial registration This trial is registered as ISRCTN10134725; ClinicalTrials.gov number NCT01506986. Funding This award was funded by the National Institute for Health and Care Research (NIHR) Health Technology Assessment programme (NIHR award ref: 09/55/52) and is published in full in Health Technology Assessment; Vol. 29, No. 42. See the NIHR Funding and Awards website for further award information.